Laudato Si': a bridge towards access to medicines - Jorge Antonio Zepeda Bermudez; Adriana Mendoza-Ruiz; Sandra Pereira Soares; Mansur Ferreira Campos; Ana Paula Oliveira Brum; Silvania Iacovino Dantas; Jorge Carlos Santos da Costa (Fundação Oswaldo Cruz (FIOCRUZ), 2018)
Pope Francis' Encyclical Laudato Si', albeit not explicitly, has drawn attention worldwide to the access to medicines as a fundamental human right, as it raises awareness about the current situation of the world and the poor. The reflections set forward by the Encyclical Laudato Si' bring us to the intersections between trade and health care, and how to correctly frame the need for innovation, affordable and accessible health technologies to those in need and how to reach the poorest of the poor. The issues of how to provide access, promote innovation, stimulate reasonable competitive market forces and ensure viable supply are central to the question of how to address Universal Human Rights. Also in this context, intellectual property has gained particular significance with increased attention to new essential medicines for the treatment of diseases of global incidence, including communicable and non-communicable diseases. This article intends to bring elements for a reflection on the debate on universal access to medicines.